1992
DOI: 10.1161/01.cir.86.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the angiotensinogen gene and localization of its protein in the human heart.

Abstract: We conclude that angiotensinogen was synthesized in the human heart. It was evident that the localization of angiotensinogen was not ubiquitous in the cardiac muscles, showing its predilection for the atrial muscles, muscles of the conduction system, and subendocardial layer of the left ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Angiotensinogen mRNA has been detected in cardiac tissue homogenates." 12 Are the cardiac Ang I and II levels we measured the true in vivo levels? We took precautions to prevent the ex vivo generation and breakdown of angiotensins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensinogen mRNA has been detected in cardiac tissue homogenates." 12 Are the cardiac Ang I and II levels we measured the true in vivo levels? We took precautions to prevent the ex vivo generation and breakdown of angiotensins.…”
Section: Discussionmentioning
confidence: 99%
“…5 Angiotensinogen mRNA and angiotensinogen have been detected in rat" and human 12 cardiac tissue as well as in cultured myocytes and fibroblasts from neonatal rat hearts. 5 It has also been reported that angiotensinogen is released by the isolated perfused rat Langendorff heart, 13 but it remains to be proved that this angiotensinogen was not derived from plasma.…”
mentioning
confidence: 99%
“…21 Briefly, the cells or sections were incubated in methanol containing 0.25% H 2 O 2 for 15 minutes. After washing with PBS, they were incubated with normal serum for 30 minutes (horse serum for assay of HHF-35 and RAM-11 and goat serum for assay of PAI-1 antigen, factor Vlll-related antigen, and thrombomodulin), primary antibody (60 minutes), biotinylated second antibody (60 minutes at 37°C), and avidin-biotin peroxidase complexes (30 minutes).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In both canine and human ventricle, I to density is higher in epicardial and midmyocardial than in the endocardial cells (17,18). The gradient of I to inversely correlates with the gradient of angiotensinogen across the ventricular wall whose expression is more prominent in the subendocardial than in either midmyocardium or epicardium regions (20). Evidence exists that cardiomyocytes, Purkinje fibers, and cardiac fibroblasts produce angiotensin II (21)(22)(23).…”
mentioning
confidence: 99%